Electric vehicle and agent bidding method thereof - LIU SHU; ZHANG QIUQIAO; WANG MIN; FANG CHEN; LIU WEIYANG; BAO HAILONG; WANG HAOJING; SHI SHANSHAN; WANG BING; ZHOU JIAN (2021)
The invention discloses an electric vehicle and an agent bidding method thereof. The method comprises the following steps: S1, clustering user travel time and classifying the initial residual electric quantity of the electric vehicle by using a K-means clustering algorithm and a quartile method; S2, establishing an electric vehicle user and agent bidding interaction model, and integrating large-scale charging and discharging resources; S3, establishing a bidding interaction model between the agent and a power dispatching center, wherein the power dispatching center aims at optimizing the load of a power grid and optimizing the benefit of a power grid company to reduce the operation cost of the system; S4, providing an electric vehicle agent bidding algorithm based on double-layer optimization, taking the charging and discharging electricity price and the electric quantity obtained through electricity market bidding as an outer-layer optimization model, taking the benefit balance among the market subjects as a